2019
DOI: 10.1002/pca.2839
|View full text |Cite
|
Sign up to set email alerts
|

Separation of α‐glucosidase inhibitors from Potentilla kleiniana Wight et Arn using solvent and flow‐rate gradient high‐speed counter‐current chromatography target‐guided by ultrafiltration HPLC‐MS screening

Abstract: Introduction Potentilla kleiniana Wight et Arn is widely used as a herbal medicine to treat type 2 diabetes. However, detailed information about its active compounds is lacking. Objective To develop an efficient method for the rapid screening and separation of α‐glucosidase inhibitors from Potentilla kleiniana Wight et Arn. Methodology Potential α‐glucosidase inhibitors from Potentilla kleiniana Wight et Arn were rapidly screened out through ultrafiltration high‐performance liquid chromatography mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Generally, a suitable composition for the twophase solvent system is crucial for a perfect HSCCC separation, which relied on satisfactory partition coefficient (K D ) values ranging from 0.5 to 2.0 for the target components. 25,26 Previous studies have identified the flavonoids from the thorns of G. sinensis mainly as flavonoid aglycones as well as a few flavonoid glycosides. Thus, several solvent systems of n-hexane-ethyl acetatemethanol-water, n-hexane-ethyl acetate-n-butanol-water, chloroform-methanol-water, dichloromethane-methanol-water, and dichloromethane-methanol-n-butanol-water with different composition ratios, were applied for testing the K D values of the five main constituents (1)(2)(3)(4)(5) in the DES extracts (Table 2).…”
Section: Optimisation Of Two-phase Solvent Systems For Des Extracted Flavonoids By Hscccmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a suitable composition for the twophase solvent system is crucial for a perfect HSCCC separation, which relied on satisfactory partition coefficient (K D ) values ranging from 0.5 to 2.0 for the target components. 25,26 Previous studies have identified the flavonoids from the thorns of G. sinensis mainly as flavonoid aglycones as well as a few flavonoid glycosides. Thus, several solvent systems of n-hexane-ethyl acetatemethanol-water, n-hexane-ethyl acetate-n-butanol-water, chloroform-methanol-water, dichloromethane-methanol-water, and dichloromethane-methanol-n-butanol-water with different composition ratios, were applied for testing the K D values of the five main constituents (1)(2)(3)(4)(5) in the DES extracts (Table 2).…”
Section: Optimisation Of Two-phase Solvent Systems For Des Extracted Flavonoids By Hscccmentioning
confidence: 99%
“…It was noted that extraction with DES-1 achieved a higher yield of flavonoids with peaks 1-4 being 51.6%, 69.8%, 59.1%, and 28.6% higher than the control sample, respectively, while peak 5 being 26.7% less than the control sample. Overall, DES-1 was identified as the most efficient alcohol-based DES for the flavonoids.F I G U R E 1 HPLC chromatogram of flavonoids from the thorns of Gleditsia sinensis at 300nm, extracted by means of different eutectic solvents DES1DES5, and a control extract obtained with methanolwater (75:25)…”
mentioning
confidence: 99%
“…16,17 Compared with immobilised enzyme screening assay, complex synthesis procedures can be avoided. 18,19 PC12 rat pheochromocytoma cells have been widely used as cellular models of neurodegenerative diseases. 20 Aβ is widely considered to play a central role in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in vitro evaluation methods are fast and require only a small amount of samples, making them suitable for analysing a wide variety of active components found in foods and herbs. To overcome these limitations and enhance drug discovery throughput, molecular methods based on high‐affinity and high‐selectivity protein–ligand interactions have been successfully applied 20 . In particular, combined ultrafiltration‐liquid chromatography‐mass spectrometry (UF‐LC–MS) is a powerful method for screening a wide range of biologically active compounds from botanical extracts because the UF step facilitates the separation of ligand–receptor complexes from unbound compounds, while the subsequent LC–MS step can identify the ligands 21 …”
Section: Introductionmentioning
confidence: 99%